The STRATEGI PENANGGULANGAN STUNTING MELALUI SEKOLAH SIAGA KEPENDUDUKAN - Eko Rizqi Purwo Widodo (University of Muhammadiyah Malang, 2022)
The study focuses on describing the implementation of a population alert school as a stunting prevention strategy in Malang Regency. The research method employed is descriptive qualitative, with six informants participating in the study. Data collection involved interviews, observation, and documentation, while data analysis encompassed data collection, data reduction, data presentation, and drawing conclusions. The findings of the study are as follows: Population Alert Schools have been implemented in Malang Regency since 2019. The Population Alert School curriculum has been integrated into the existing school curriculum. Several schools have organized activities known as SSK (abbreviated from Population Alert School in Indonesian). The primary objective of implementing population alert schools is to prevent an increase in stunting rates in Malang District. However, the implementation of population alert schools faces obstacles, with one notable challenge being the lack of universal adoption by all schools in Malang District. Based on the study's results, several suggestions are proposed: Optimize SSK activities further to enhance their effectiveness in addressing stunting. Transform SSK activities into regional policies to ensure mandatory implementation in all schools, considering the ongoing prevalence of stunting in Malang Regency. Foster collaboration between the government and the community to reduce stunting more effectively, thereby achieving the desired goal. These recommendations aim to improve the implementation of population alert schools and enhance efforts to combat stunting in Malang Regency.